Investigating Factors Impacting Hospitalization Duration in COVID-19 Patients: A Retrospective Case-Control Study in Jordan - Al-Ibadah, Mahmood; Al-Qerem, Walid (Jordan Journal of Pharmaceutical Sciences, 2025)
Objective: Coronavirus disease 2019 (COVID-19) is a severe acute respiratory illness of the upper respiratory tract. Evaluating the variables that influence the period of hospitalization and complications in COVID-19 patients can help effectively and safely decrease undesirable events. Therefore, the present study aimed to evaluate parameters influencing the length of hospital stay (LOS) in COVID-19 patients. Patients and Methods: A retrospective case-control study involving hospitalized patients due to COVID-19. Demographic information, clinical treatment, and laboratory data were obtained from their medical records. Laboratory assessments included C-reactive protein (CRP), D-Dimer, lactate dehydrogenase (LDH), ferritin, urea, creatinine, estimated glomerular filtration rate (eGFR), uric acid, and complete blood count. Statistical analyses involved bivariate and multivariate logistic regressions to identify predictors of prolonged LOS. Results: The median LOS for 83 patients was 7 days (IQR = 6–8). The median age of the patients was 58 years. Approximately half the patients were in the high-risk group (44.6%). The multivariate logistic regression analysis revealed that high neutrophil count (AOR = 1.144 95% CI 1.059–1.236, p = 0.001) increased the odds of prolonged LOS. In contrast, high creatinine levels decreased the odds of prolonged LOS (AOR 0.431, 95% CI 0.211–0.880, p = 0.021). Conclusions: LOS was associated with increased neutrophil and decreased creatinine. Understanding these factors can assist in optimizing care and resource allocation in hospitals during health crises.